Iron status in breast-fed infants - I Gusti Ayu Asih Ratnadi; Soetjiningsih Soetjiningsih (Indonesian Pediatric Society, 2001)
Ninety infants were selected stratified proportionally random sampling and they met the inclusion criteria. Iron status was determined by the serum ferritin level concentration. The nutritional status was determined by the body weight to age based on the standard criteria of WHO NCHS. The quality of food was defined by asking the parents to keep a diary of consumed in the last 7 days minimally for three days. Out of the 90 infants, 50.4 % of them were males and 45.6 % of them were females. Most of them (93.7%) had normal nourished and 8.3 % had undernourished. The prevalence status of low iron was 18.9%. The low iron status began to occur at the age of 4 – 6 months old (6%) and the highest at the age of 9 – 12 months old (65%). Statistically significant differences were found between the iron status and the quality of food supplements over age group. The low quality of food is a risk factor influence the status of low iron. It is suggested that the iron supplements be given to breast-fed infant at the age of 4 – 6 months old.